An assessment of the legal framework governing land ownership is evolving in ukraine. (2022) - Yuliia, Krasnova; Liudmyla, Golovko; Liudmyla, Hunko; Nataliia, Medynska; Gupta, Sandeep Kumar
Abstract: The experience of carrying out reforms in the field of property relations regulation both in Ukraine and other countries shows the need to develop clear concepts taking into account the specifics of the country. Nowadays, we often find that the laws governing the institution of property rights, especially land ownership, do not meet the real needs of the producer of agricultural products. That is why the absence of contradictions between the demands of the population and existing legislation must be achieved at the legislative level. The article examines the development of legal regulation of land ownership in Ukraine. The process of reforming property relations in Ukraine since 1991 has been studied, in particular: the privatization process, the mechanism of acquiring property rights to real estate, registration of property rights and other rights to real estate, legal regulation of land cadastre. Legal regulation of the ownership of agricultural land in some EU member states is revealed. Using the forecasting method, the authors formulated recommendations for improving the legal regulation of land ownership in Ukraine.